Diminishing returns of additional active travel infrastructure: Evaluating Barcelona's decade of sustainable transportation progress - Jaime Orrego-Oñate; Marta-Beatriz Fernández Núñez; Oriol Marquet (Journal of Urban Mobility)
In the context of the urgent climate crisis in urban areas, transportation policymakers are actively working to shift from car travel to sustainable transportation options through strategic interventions in the built environment. These efforts often involve a dual approach: promoting higher activity density to increase proximity to destinations while enhancing the experience of active mobility. However, a notable gap exists in addressing densely populated areas with established built environments, where the focus remains primarily on improving active mobility infrastructure. This study represents a crucial initial step in tackling this challenge. It examines mode distribution trends and trip purposes in Barcelona, an urban area that has recently seen significant enhancements in active mobility spaces. Our study sheds light on evolving modal share trends by analyzing local travel surveys from 2010 to 2019. The findings reveal relatively unchanged patterns in travel behavior at the city level during the examined years. Nevertheless, a closer examination of mode distribution for specific trip purposes, age ranges, and gender exposes noticeable shifts. The newly implemented infrastructure may have helped prevent a shift from active mobility to car usage, particularly for trips traditionally associated with public transit or walking, such as accessing public or health services. Further research is needed to explore this hypothesis and determine the extent of its impact.